Mentoring Development of AI-assisted Ethnoscience-Based Students Worksheet for Independent Learning: Pendampingan Pengembangan LKPD Berbasis Etnosains Berbantuan AI Untuk Mewujudkan Merdeka Belajar - Rumtutuly, Fransheine; Kurniati MA, Ratnah; Lekitoo, John Nandito; Lestari, Lestari; Dolewikou, Rina; Dolaitery, Demianus Adrian; Kwuwulay, Hermina; Sairtory, Difia; Miru, Juandi (Universitas Lancang Kuning, 2025)
The mentoring program for the development of AI-assisted ethnoscience-based LKPD at SD Negeri Tiakur aims to enhance teachers' skills in designing LKPD that are relevant to the local culture. This training is motivated by the low utilization of technology in learning in border areas such as the Maluku Barat Daya Regency, as well as the insufficient integration of local culture in the learning process. The methods employed include socialization, training, evaluation, and program sustainability. The evaluation results show an 81% improvement in teachers' skills based on the N-gain test. This program has produced attractive, interactive, and contextual LKPD, blending local cultural elements such as traditional dances, weaving, and the koli tree with modern scientific concepts. The use of technology tools such as Canva and Quizizz has made it easier for teachers to design and evaluate LKPD. This program not only improves the effectiveness of learning but also promotes the preservation of local wisdom and supports the achievement of inclusive, high-quality, and contextual education.